2012
DOI: 10.1016/j.clinbiomech.2011.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lateral epicondylosis on upper limb mechanical parameters

Abstract: Background Lateral epicondylosis is a prevalent and costly musculoskeletal disorder characterized by degeneration of the common extensor tendon origin at the lateral epicondyle. Grip strength is commonly affected due to lateral epicondylosis. However, less is known about the effect of lateral epicondylosis on other functional parameters such as ability to react to rapid loading. Methods Twenty-nine lateral epicondylosis participants and ten controls participated in a case-control study comparing mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Of these, 25 satisfied the selection criteria and reported bilateral nociceptive, sensory and motor measures of participants with unilateral tendinopathy contrasted with data for controls (figure 1). Two studies were excluded as they reported secondary presentation of data published elsewhere 15 16. Seven authors were contacted during data extraction to provide additional information for the following reasons: data only presented graphically17; affected and unaffected limb data combined18–20; no control data for a specific outcome measure21 and insufficient details for data 22 23.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 25 satisfied the selection criteria and reported bilateral nociceptive, sensory and motor measures of participants with unilateral tendinopathy contrasted with data for controls (figure 1). Two studies were excluded as they reported secondary presentation of data published elsewhere 15 16. Seven authors were contacted during data extraction to provide additional information for the following reasons: data only presented graphically17; affected and unaffected limb data combined18–20; no control data for a specific outcome measure21 and insufficient details for data 22 23.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical parameter results are reported elsewhere. 11 The study was a case-control study comparing sensorimotor and motor performance of injured and uninjured upper extremities using data collected in participants with LE (+LE) compared to healthy, uninjured controls (−LE).…”
Section: Methodsmentioning
confidence: 99%
“…6-8 LE may affect the muscle fiber type composition 9 , neural drive 10 and stiffness of the muscle tendon complex. 11,12 Pain at the lateral aspect of the elbow is a primary symptom of LE. 13 This pain is often exacerbated by gripping activities with grip strength often impaired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 25 satisfied the selection criteria and reported bilateral nociceptive, sensory and motor measures of participants with unilateral tendinopathy contrasted with data for controls . Two studies were excluded as they reported secondary presentation of data published elsewhere (Alizadehkhaiyat et al, 2009;Chourasia, Buhr, Rabago, Kijowski, & Sesto, 2012b). Seven authors were contacted during data extraction to provide additional information for the following reasons: data only presented graphically (Strizak, Gleim, Sapega, & Nicholas, 1983); symptomatic and asymptomatic limb data combined (Crossley et al, 2007;Dauty, Dupré, Potiron-Josse, & Dubois, 2007;du Toit et al, 2008); no control data for a specific outcome measure (Fernández-Carnero, Fernández-De-Las-Peñas, De La Llave-Rincón, Ge, & Arendt-Nielsen, 2008) and insufficient details for data (Bisset et al, 2006b;Gaida, Cook, Bass, Austen, & Kiss, 2004).…”
Section: Database Searchmentioning
confidence: 99%